Optimizing Poetry Writing and Creative Thinking Skills through the Integration of AI-Assisted CTL with ChatGPT-4 - Dewi Sartika Panggabean; Aripin Rambe; Tesalonika Br. Tampubolon; Trisno Benaya Gea (Raja Zulkarnain Education Foundation, 2026)
This study aims to examine the effectiveness of integrating the Contextual Teaching and Learning (CTL) model assisted by ChatGPT-4 artificial intelligence in optimizing elementary school students' poetry writing and creative thinking skills. A quantitative approach with a quasi-experimental Non-Equivalent Control Group Design was used in this study, involving two classes as the experimental and control groups. The research instruments were developed based on the dimensions of poetry writing and creative thinking, validated for content and reliability through statistical approaches. Data collection was conducted through pretest and posttest, then analyzed using JAMOVI and JASP for independent t-tests, normality, homogeneity, and effectiveness calculation through N-Gain. The results of the study indicate a highly significant difference (p < 0.001) in all ability indicators between the experimental and control groups, with a substantial increase in average scores in the group that received the CTL and ChatGPT-4 intervention. This integration was proven to encourage high achievement in aspects of poetry structure, diction, originality, and creative thinking dimensions such as fluency, elaboration, and flexibility. These findings indicate that contextual learning enriched with generative technology can create a reflective, adaptive, and transformative learning ecosystem. The conclusions of this study affirm that the integrative approach of CTL and generative AI is not only pedagogically effective but also makes a significant contribution to strengthening creative literacy and the development of the Pancasila Student Profile. This study recommends the widespread implementation of this model in learning based on the Merdeka Curriculum